A quantitative global review of species population monitoring. Issue 1 (1st June 2021) - Moussy, Caroline; Burfield, Ian J.; Stephenson, P. J.; Newton, Arabella F. E.; Butchart, Stuart H. M.; Sutherland, William J.; Gregory, Richard D.; McRae, Louise; Bubb, Philip; Roesler, Ignacio; Ursino, Cynthia; Wu, Yanqing; et al.
Abstract: Species monitoring, defined here as the repeated, systematic collection of data to detect long‐term changes in the populations of wild species, is a vital component of conservation practice and policy. We created a database of nearly 1200 schemes, ranging in start date from 1800 to 2018, to review spatial, temporal, taxonomic, and methodological patterns in global species monitoring. We identified monitoring schemes through standardized web searches, an online survey of stakeholders, in‐depth national searches in a sample of countries, and a review of global biodiversity databases. We estimated the total global number of monitoring schemes operating at 3300–15, 000. Since 2000, there has been a sharp increase in the number of new schemes being initiated in lower‐ and middle‐income countries and in megadiverse countries, but a decrease in high‐income countries. The total number of monitoring schemes in a country and its per capita gross domestic product were strongly, positively correlated. Schemes that were active in 2018 had been running for an average of 21 years in high‐income countries, compared with 13 years in middle‐income countries and 10 years in low‐income countries. In high‐income countries, over one‐half of monitoring schemes received government funding, but this was less than one‐quarter in low‐income countries. Data collection was undertaken partly or wholly by volunteers in 37% of schemes, and such schemes covered significantly more sites and species than those undertaken by professionals alone. Birds were by far the most widely monitored taxonomic group, accounting for around half of all schemes, but this bias declined over time. Monitoring in most taxonomic groups remains sparse and uncoordinated, and most of the data generated are elusive and unlikely to feed into wider biodiversity conservation processes. These shortcomings could be addressed by, for example, creating an open global meta‐database of biodiversity monitoring schemes and enhancing capacity for species monitoring in countries with high biodiversity. Article impact statement : Species population monitoring for conservation purposes remains strongly biased toward a few vertebrate taxa in wealthier countries. Abstract : Una Revisión Global Cuantitativa del Monitoreo Poblacional de Especies Resumen: El monitoreo de especies, definido aquí como la recolección sistemática y repetida de datos para detectar cambios a largo plazo en las poblaciones de las especies silvestres, es un componente vital de la práctica y las políticas de la conservación. Generamos una base de datos de casi 1, 200 esquemas, con un rango de fecha de inicio desde 1800 hasta 2018, para revisar los patrones espaciales, temporales, taxonómicos y metodológicos en el monitoreo global de especies. Identificamos los esquemas de monitoreo por medio de búsquedas estandarizadas en línea, una encuesta digital realizada a los actores, búsquedas a profundidad en una muestra de países y en una revisión global de las bases de datos sobre la biodiversidad. Estimamos el número total mundial de esquemas funcionales de monitoreo entre 3, 300 y 15, 000. Desde el 2000, ha habido un fuerte aumento en el número de esquemas nuevos que han iniciado en países de bajo o mediano ingreso y en países megadiversos, pero una disminución en los países de alto ingreso. El número total de esquemas de monitoreo en un país y su producto interno bruto per cápita tuvieron una correlación sólida y positiva. Los esquemas que estaban activos en 2018 lo habían estado en un promedio de 21 años en los países de alto ingreso, comparado con un promedio de 13 años en los países de mediano ingreso y de 10 años en los países de bajo ingreso. En los países de alto ingreso, más de la mitad de los esquemas de monitoreo recibieron financiamiento del gobierno, comparado con menos de un cuarto de los esquemas en los países de bajo ingreso. La recolección de datos se realizó parcial o totalmente por voluntarios en 37% de los esquemas, y dichos esquemas cubrieron significativamente más sitios y especies que aquellos realizados sólo por profesionales. Las aves fueron por mucho el grupo taxonómico más monitoreado, comprendiendo casi la mitad de todos los esquemas, pero este sesgo declinó con el tiempo. El monitoreo en la mayoría de los grupos taxonómicos todavía es disperso y descoordinado, y la mayoría de los datos generados son vagos y tienen poca probabilidad de alimentar procesos más amplios de conservación de biodiversidad. Estas deficiencias podrían abordarse, por ejemplo, creando una meta‐base de datos globales abiertos de los esquemas de monitoreo de la biodiversidad y mejorando la capacidad para el monitoreo de especies en los países con alta biodiversidad. 摘要: 物种监测, 在本文中指重复、系统地收集数据以检测野生物种种群的长期变化, 是保护实践和政策的重要组成部分。我们创建了一个包含近 1200 项计划的数据库, 计划开始时间覆盖 1800–2018 年, 以综述全球物种监测的空间、时间、类群及方法的模式。这些计划是通过标准化网络搜索、利益相关者在线调查、一系列国家样本的深度搜索, 以及对全球生物多样性数据库的综合考察确定的。我们估计全球范围内开展的监测计划总数在 3, 300–15, 000 之间。自 2000年以来, 低收入和中等收入国家以及高生物多样性国家开启新计划的数量急剧增加, 而高收入国家中则有所下降。一个国家的监测计划总数与其人均国内生产总值之间存在着强烈的正相关关系。在高收入国家中, 2018 年仍在进行的计划平均已开展 21 年, 在中等收入国家中为 13 年, 而在低收入国家中为 10 年。高收入国家超过一半的监测计划都获得了政府资助, 而在低收入国家, 这一比例不足四分之一。数据收集部分或全部由志愿者完成的计划占 37%, 它们覆盖的地点和物种远远多于仅由专业人员参与的计划。到目前为止, 得到监测最广泛的类群是鸟类, 约占所有计划的一半, 但这种偏倚正在随时间推移而减弱。然而, 对大多数类群的监测仍十分稀少且不对等, 产生的数据大多难以理解, 不太可能用于更广泛的生物多样性保护过程。最后, 我们提出了一些方法来解决以上缺点, 如建立开放的全球生物多样性监测计划元数据库, 以及加强高生物多样性国家的物种监测能力。【翻译 : 胡怡思 ; 审校 : 聂永刚】